+0  
 
0
266
2
avatar

2(7b−6)−5(2b−3)

off-topic
 Apr 22, 2019
edited by Guest  Apr 22, 2019
 #1
avatar+20 
+1

Expand. \(2\cdot7b=14b\)

\(2\cdot-6=-12.\)

\(-5\cdot2b=-10b\)

\(-5\cdot-3=15\)

 

Add up all the terms and get...

\(4b+3\)

 Apr 22, 2019
 #2
avatar+219 
-2

To simplify this expression, first expand the four terms(in total) in the parantheses. When expanded, you get 14b - 12 - 10b + 15. Simplify this to get 4b + 3.

 

The simplified expression is 4b+3.

 

~~Hypotenuisance

 Apr 23, 2019

21 Online Users

avatar